Alcohol use, intimate partner violence, and HIV sexual risk behavior among young people in fishing communities of Lake Victoria, Uganda - Stephen Ojiambo Wandera; Nazarius Mbona Tumwesigye; Eddy J. Walakira; Peter Kisaakye; Jennifer Wagman (BMC, 2021)
Abstract Background Few studies have investigated the association between alcohol use, intimate partner violence, and HIV sexual risk behavior among young people in fishing communities from eastern and central Uganda. Therefore, we aimed to determine the association between alcohol use, intimate partner violence, and HIV sexual risk behavior among young people in the fishing communities on the shores of Lake Victoria, in Uganda. Methods We conducted multivariable logistic regression analyses of HIV risk behavior using cross-sectional data from 501 young people from Mukono (Katosi landing site) and Namayingo districts (Lugala landing site). Results Almost all (97%) respondents reported at least one HIV risk behavior; more than half (54%) reported engagement in three or more HIV risk behaviors. Results from the adjusted model indicate that alcohol use, working for cash or kind, being married, and having multiple sexual partners increased the odds of HIV risk behavior. IPV was not associated with HIV risk behavior. Conclusion Interventions to promote consistent condom use and fewer sexual partnerships are critical for young people in the fishing communities in Uganda.